Management Of Community Learning Activity Centers In Fostering Independence Of Learning Citizens Package C Through Lifeskill Education - Roro Vemmi Kesumadewi, Raden; Wasliman, Iim; Suhendraya Muchtar, Hendi; Koswara, Nandang (CV. Inara, 2022)
PKBM is currently being developed by various parties, both by the community, social and religious institutions (organizations), or formed by the government, especially the District/City Education Office, District through Community Education Inspectors, even at the Village/Kelurahan level. However, the problems that surround it continue to occur, this is due to the large number of PKBMs that are not established on the basis of the community's need, but are built on the basis of the interest of absorbing government programs only. In addition, PKBM has not really played a role as a facilitator who empowers the community. In fact, there are still many PKBMs that were engineered to encourage people to establish PKBM. The research approach used is qualitative. The data collection method used is the case study method. Data collection techniques used are observation techniques (observations), interview techniques, documentation studies, bibliographic studies (library studies) and participation. Based on the results of research findings, interpretations and discussions, it is concluded that PKBM Management in Fostering Independence of Learning Citizens Package C through Lifeskill Education through the stages of planning, organizing, implementing and evaluating, is not optimal because there are still weaknesses in Sempurna PKBM and Al Hikmah PKBM. Meanwhile, the results of the study indicate that PKBM Management has not been developed fundamentally either based on curriculum theory, national system qualification rules and lifelong learning achievements as the basis for implementing PKBM management which is the basic orientation of implementing life skills education in PKBM. Activities carried out in planning begin with the teacher analyzing KI/KD, syllabus, teacher books and student books. The organization of learning materials is made in balance between the competence of attitudes, knowledge and skills, so that students can master the material theoretically, have an honest attitude, have character, taqwa, be creative and be devoted to both parents. Implementation of the learning process with the steps of learning activities according to the syllabus, teacher's book and lesson plans, including very good qualifications. The problem faced is the availability of PKWU learning time allocation which is only two hours of lessons in one week and the lack of synchrony between education at home and in PKBM. The solution in overcoming these problems is that PKBM makes every effort to fortify students and all elements in PKBM with noble character and positive character of independence through well-programmed habituation and exemplary activities and PKBM strives to continue to develop an independent curriculum based on independence skills, noble character, skilled and have a good future.